Interfaces of intestinal stomas in life cycles - Pedrosa, Pietro Henrique Benevides; Souza, Érica Motta Moreira de; Ribeiro, Wanderson Alves; Oliveira, Ane Raquel de; Siqueira, Milena Rangel; Carneiro, Ana Fagundes; Grassel, Cristal dos Santos; Klein, Lorena Costa; Guedes, Miriam Maria Ferreira; Constantino, Gabriel Nivaldo Brito; Pires, Tarsila Reis Pinto; Santos, Daiane Lopes dos; et al. (Brazilian Journal of Science, 2024)
The term Quality of Life, despite not having a consensual definition, is based on the individual perception of a complete physical, mental and social well-being that permeates a dynamic, broad, subjective and polysemic concept. The individual with a stoma needs post-operative care and help with day-to-day tasks, in addition to self-care and social interactions to remain psychologically and physically healthy, as there are numerous changes in habits and routine of life. From this perspective, the following question arises for the study: What are the impacts of the ostomy in the different life cycles? The objective of this research is to analyze the repercussion of making an intestinal stoma in patients at different stages of life, contributing to the updating of knowledge in multiple assertions. This is a descriptive, qualitative study of the reflective analysis type, based on a literature review on the “interfaces of intestinal ostomies in life cycles”. For that, a narrative review was carried out. Narrative review studies are publications with the purpose of describing and discussing the state of the art of a given subject. The results obtained through the literature review allow us to say that the quality of life of people with a stoma is a fundamental aspect for their physical, emotional and social health. In each life cycle, people with a stoma face specific challenges that affect their routine and their way of relating in society. Finally, it is important to highlight that the quality of life of people with ostomies is not just a matter of choosing the ideal device, but also access to adequate health care and public policies that guarantee access to quality devices and materials. It is important that these individuals are always monitored by a multidisciplinary team, along with a family support network providing self-care and maintenance of their self-image.